Exploration of neuropeptides to identify potential target for regulating feeding behavior and development in Eurygaster integriceps - Mehrbanoo Kazemi Alamouti; Mohammad Majdi; Reza Talebi; Mehdi Dastranj; Aziz Sheikhigarjan; Mohsen Mardi; Alireza Bandani; Zahra Ghorbanzadeh; Ghasem Hosseini Salekdeh; Mohammad Reza Ghaffari (PLoS ONE, 2026)
Neuropeptides regulate diverse physiological processes in insects, including feeding, reproduction, and development, and have therefore emerged as promising species-specific targets for next-generation pest control strategies. In this study, we focused on 13 feeding-related neuropeptides previously identified from our whole-body RNA-seq dataset of Eurygaster integriceps . Using a combination of bioinformatics and expression analyses, we characterized precursor structures, predicted mature peptides, and quantified expression across developmental stages, between sexes, and in key feeding-associated organs of head and gut. Several neuropeptides, including Ast-A , Ast-B , Ast-C , AKH , SIF , ITP , Burs , sNPF , NPF , and Crz showed higher expression in males than in females, suggesting sexually dimorphic regulation of feeding and metabolism. Moreover, most neuropeptides were expressed at higher levels in the head compared to the gut, which is consistent with central neuro-regulatory functions. Furthermore the expression pattern of neuropeptides of life cycle developmental stages revealed peak expression in early developmental stages, along with stage-specific variation indicating coordinated regulation of growth, feeding behavior, and digestive physiology. Taken together, these findings provide the first detailed molecular and expression atlas of feeding-related neuropeptides in E. integriceps and offer foundational insights for developing future neuropeptide-based, species-specific, and environmentally safe biocontrol strategies.